Peranan Insentif terhadap Kinerja Karyawan PT Haleyora Power Rayon Cikembar Kabupaten Sukabumi - Faisal Rizky Sabani; Erry Sunarya (Journal of Management and Bussines (JOMB), 2020)
The purpose of this study was to determine the effect of incentives on employee performance. The method used in this research is to use descriptive and associative methods. Data collection techniques used by researchers in this study are through observation, questionnaire interviews, documentation and literature studies. The results of the calculation of the hypothesis test t arithmetic ab t abel is 14.071 ≥ 1.997. Conclusion, there is a significant influence between incentives on employee performance. Keywords: Incentives, Employee Performance